Analysis of Student Learning Independence in Distance Learning at Madrasah Aliyah Negeri: A Review of Self-Concept in Urban and Rural Areas of South Kalimantan Province - Maulida Hayatina; Salina Ahdia Fajrina; Muslem Muslem (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to find out the difference in learning independence of MAN learners in Distance Education in urban and rural areas after being controlled by self-concept variables. The approach in this research is a quantitative approach using survey methods. The sample in this study amounted to 392 students who attended school in the urban and rural areas of South Kalimantan Province. Data collection techniques in this study use questionnaires and documentation. The questionnaire instrument is theoretically validated using the Delphi technique while empirically using a static test of factor analysis. As for testing the hypothesis, the requirements test is carried out as follows: (1) normality test; (2) homogeneity test; and (3) linearity test, which is then followed by a covariance analysis test (ANAKOVA). The results of this study proved that there was no significant difference in the learning independence of MAN learners in PJJ between urban and rural areas after controlled self-concept variables. However, if you look at the magnitude of the influence, it is known that there is a significant influence on self-concept on the learning independence of MAN students in PJJ in urban and rural areas of South Kalimantan Province.